THE EFFECT OF MANAGERIAL COMPETENCE AND PRINCIPAL SUPERVISION - Yaqin, Muhib Ainul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out the effect of the school principals’ managerial and supervisory competeonward teacher performance in SMK Al-Furqon. This research is field research using a quantitative approach. Data collection was carried out by observing and distributing questionnaires. Based on the results of the research that has been done, it can be concluded that the school principal’s managerial competence in SMK Al-Furqon Bondowoso is included in the very good category with a percentage value of 80%. Furthermore, the school principal’s supervisory competence is included in the very good category with a percentage value of 75%. Teacher performance is also included in the very good category with a percentage value of 85%. In addition, there is no effect of the school principal's managerial competence on teacher performance in SMK Al-Furqon Bondowoso. This was concluded based on calculations using the tcount test with a significance value of 0.271 > 0.05, and the results of count 1150 <2.109, then H0 is accepted and Ha is rejected. There is also no effect of the school principal's supervisory competence on teacher performance. This was concluded based on calculations using the count test with a significance value of 0.271 > 0.05, and the results of count 1150 <2.109, then H0 is accepted and Ha is rejected. Conversely, based on calculations that have been carricounted out using the F test (Simultaneous) with a significance value of 0.000 <0.05 and the results of Fcount 74.539 > 3.55 or Fcount > Ftable, then H0 is rejected and Ha is accepted, indicating that there is an effect from managerial and supervisory competence on teacher performance. The result of the coefficient of determination (R2) is 0.898. Thus, the effect of the school principal’s managerial and supervisory competence on teacher performance is 89%